TI_GERICHTE 15.2017.50 vom 16. August 2017 , Ricorso contro un precetto esecutivo ritenuto manifestamente abusivo - TI Tribunale d'appello (2017)
Ricorso contro un precetto esecutivo ritenuto manifestamente abusivo